UJI PERTUMBUHAN DAN DAYA HASIL TANAMAN MUTAN (M2) CABAI RAWIT - Anugrah Palupi, Delvia Dipta; Makhziah, Makhziah; Sukendah, Sukendah (Fakultas Pertanian, Universitas Janabadra, 2024)
Public demand for cayenne pepper is high. To continue to meet public demand, superior varieties are being assembled to obtain cayenne pepper plants with high yields. Breeding efforts in assembling superior varieties can be carried out using gamma ray irradiation techniques. This research was carried out with the aim of determining whether there were differences in mutant accessions resulting from irradiation compared to plants without radiation in order to determine whether there were accessions with superior characteristics in growth and yield. The research was conducted at UPN